Impact of antiphospholipid antibodies on cardiac valve lesions in systemic lupus erythematosus: a systematic review and meta-analysis - Chen, Siyun; Zhou, Yangzhong; Wang, Chuhan; Jiang, Hui; Zhao, Yuan; Zhao, Jiuliang; Huang, Can; Li, Mengtao; Zhao, Yan (Clinical and experimental medicine, 2024)
This meta-analysis assesses antiphospholipid antibodies’ (aPLs) impact on heart valve disease in Systemic Lupus Erythematosus (SLE) patients. We searched PubMed, Embase, Cochrane, and Web of Science up to January 2024 for comparative studies of heart valve disease in aPL-positive versus aPL-negative SLE patients. Fixed-effect or random-effect models were used to synthesize data, with I 2 and sensitivity analyses for heterogeneity and the trim-and-fill method for publication bias. Including 25 studies with 8089 patients, of which 919 had valvular changes, aPLs significantly increased the risk of heart valve disease (OR = 2.24, 95% CI: 1.58–3.18, p < 0.001). Lupus anticoagulant (LA) indicated the highest risk (OR = 4.90, 95% CI: 2.26–10.60, p < 0.001), anticardiolipin antibodies (aCL) doubled the risk (OR = 2.69, 95% CI: 1.47–4.93, p = 0.001), and anti-β2 glycoprotein I (aβ2GPI) showed a 70% increase (OR = 1.70, 95% CI: 1.17–2.45, p = 0.005). Valve-specific analysis indicated the mitral valve was most commonly involved (26.89%), with higher occurrences in aPL-positive patients (33.34% vs. 15.92%, p = 0.053). Aortic and tricuspid valve involvements were 13.11% vs. 5.42% ( p = 0.147) and 12.03% vs. 8.52% ( p = 0.039), respectively. Pulmonary valve disease was rare and similar across groups (1.01% in aPL-positive vs. 1.52% in aPL-negative). Significantly, only tricuspid valve disease showed increased risk in aPL-positive patients (OR = 2.66, 95% CI: 1.05–6.75, p = 0.039). APLs notably increase the risk of heart valve disease in SLE patients, with a pronounced effect on tricuspid valve involvement. Regular cardiac assessments for aPL-positive SLE patients are crucial for timely intervention and improved prognosis.